Paveldėtieji baltų kalbų paukščių pavadinimai ir jų atitikmenys slavų kalbose (žodžių darybos lizdai) - Navickaitė-Klišauskienė, Agnė (Baltistica, 2007)
INHERITED NAMES OF BIRDS IN BALTIC LANGUAGES AND THEIR EQUIVALENTS IN SLAVIC (DERIVATIVES AND COMPOUNDS)The article focuses on the features of the word formation, which showed up in comparing the derivatives and compounds of inherited names of birds in Lithuanian, Latvian, Belarusian and Polish. The majority of the analysed derivatives and compounds are  Lithuanian. The number of  them depends on a bird. The more popular the bird is, the more derivatives and compounds there are in that family of words. The suffixes are the most productive formants of the word formation in every language. The meanings of the suffix derivatives are similar in every language; diminutives, nomina feminina, the names of meat and places predominate. Suffixal verbs, derived from the analysed names of the birds, are a rare occurrence in each language. Composition is not a characteristic feature in the families of words under discussion, and is encountered mostly in Lithuanian.
Keywords: baltų kalbos; paukščių pavadinimai; baltų-slavų